Obesity-Related Morbidity Indicators in Children and Adolescents in the City of Tashkent, Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The issue of obesity has garnered significant attention due to several compelling factors [1-3]. Firstly, it is associated with the yearly increase in the number of individuals with excess body weight [4-5]. Secondly, obesity inevitably leads to the development of pathologies affecting various organs and systems, including cardiovascular (atherosclerosis, arterial hypertension, ischemic heart disease - IHD, metabolic syndrome), musculoskeletal (osteochondrosis, degenerative osteoarthritis), endocrine (insulin-dependent diabetes mellitus, type 2 diabetes mellitus), immune (colorectal cancer, breast cancer, prostate cancer), reproductive, and others [6-8]. There is undeniable genetic predisposition to obesity, as substantiated by epidemiological research.